Pengaruh Rasio Aditif Polietilen Glikol Terhadap Selulosa Asetat pada Pembuatan Membran Selulosa Asetat Secara Inversi Fasa - Rosnelly, Cut Meurah (Jurnal Rekayasa Kimia & Lingkungan, 2012)
Preparation of cellulose acetate (CA) membranes with ultrafiltration process had be done by phase inversion using dimethylformamide (DMF) as solvent. Poliethylene glycol (PEG) 1450 Da, as additive, was added with 10, 20, and 30% rasio of celluose acetate. The thin film of polymer solution was immersed on water bath coagulation at room temperature. The analysis of membrane morphology structure by Scanning Electron Microscope (SEM) JSM 5310 LV, Jeol-Japan showed the asymetric of membrane. The addition of PEG can improve the performance of the membrane. In resulting flux is higher than membranes without PEG. Increasing of PEG/CA ratio resulted in the higher flux with lower of rejection. The higher fluxes of water, dextran, and BSA are 146, 114, and 96 L/m2hr with 52,938 and 75,716% rejection for dextran and BSA.Keywords: cellulose acetate membranes, polyethylene glycol, ultrafiltration